In vitro cytotoxic screening of 31 crude extracts of Thai herbs on a chondrosarcoma cell line and primary chondrocytes and apoptotic effects of selected extracts - Napat Ruamrungsri (2018)
© 2016, The Society for In Vitro Biology. Thirty-one dichloromethane and methanol crude extracts of 16 herb species used in Thai traditional folk medicine were studied for their cytotoxic activities on the SW 1353 chondrosarcoma cell line and primary chondrocytes. Methyl thiazolyl tetrazolium (MTT) cell viability assay and flow cytometric method were used as screening tools for cytotoxicity testing. The half maximal inhibitory concentration (IC50) was measured and reported for each crude extract. Apoptosis, necrosis, and cell viability were measured by flow cytometry at IC50.Two out of 31 herbal extracts, methanol extracts of Paris polyphylla var. chinensis and Ficus thailandica C.C. Berg & S. Gardner, showed potent anticancer activity. They demonstrated high apoptosis induction activity in SW 1353 cells but had less effect on percentage of viability and necrosis of normal chondrocyte cells. Cytotoxic screening and apoptosis assays suggest the potential anticancer activity of some plants used in Thai traditional medicine and provide information concerning their direct effects.